2012
DOI: 10.1039/c2cc31729j
|View full text |Cite
|
Sign up to set email alerts
|

The d10 route to dye-sensitized solar cells: step-wise assembly of zinc(ii) photosensitizers on TiO2 surfaces

Abstract: Dye-sensitized solar cells have been assembled using a sequential approach: a TiO 2 surface was functionalized with an anchoring ligand, followed by metallation with Zn(OAc) 2 or ZnCl 2 , and subsequent capping with a chromophore 10 functionalized 2,2':6',2"-terpyridine; the DSCs exhibit surprisingly good efficiencies confirming the effectiveness of the new strategy for zinc-based DSC fabrication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Our group has introduced a new strategy for zinc-based DSC fabrication. In terms Table 9; measurements were repeated 2 and 7 days after sealing of the DSCs and the results confirmed that the zinc(II) complexes are stable sensitizers [106 ]. The observed efficiencies of these relatively simple zinc(II) sensitizers are extremely promising, prompting us to actively pursue suitable adaptations to the ancillary tpy ligand to enhance light-harvesting.…”
Section: Zincmentioning
confidence: 83%
“…Our group has introduced a new strategy for zinc-based DSC fabrication. In terms Table 9; measurements were repeated 2 and 7 days after sealing of the DSCs and the results confirmed that the zinc(II) complexes are stable sensitizers [106 ]. The observed efficiencies of these relatively simple zinc(II) sensitizers are extremely promising, prompting us to actively pursue suitable adaptations to the ancillary tpy ligand to enhance light-harvesting.…”
Section: Zincmentioning
confidence: 83%
“…As indicated in the Introduction, bathochromically-shifted highly absorbing Zn II complexes, i.e., by suitable dye substitution and π-conjugation, may also be useful for sensitization applications such as DSSCs. 11 In this regard, preliminary tests by the use of the in situ capping technique 11 with the ATT and MeATT ligand were discouraging and showed no noteworthy activity.…”
Section: Photocatalytic Studiesmentioning
confidence: 99%
“…Diethyl ether (100 mL) was added to the reaction mixture, and then filtered. The filtrate was concentrated in vacuo to give the title compound as a yellow oil (4.932 g, 96.14% yield [38]. To a stirred solution of dimethyl 4-methylphthalate 11 (1.891 g, 9.082 mmol) and Nbromosuccinimide (1.617 g, 9.082 mmol) in 20 mL of benzene was added benzoyl peroxide (0.0391 g, 0.2738 mmol) and the reaction mixture was refluxed for 3 h. The reaction was allowed to cool to room temperature, diluted with 100 mL of hexanes, and then filtered.…”
Section: Methodsmentioning
confidence: 99%